A Novel Mathematical Model for Quality Optimization of Textile Products During Shipment - Putri, Safira Hutama; Abdullah, Fadil; Rahmawati, Nurmalinda; Dayani, Camillana Calistafo; Kusumadewi, Afriani (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2024)
The process of shipping products in the textile industry is essential as it determines the effectiveness of the business. However, non-ideal shipping can result in damage to the shipped products. Therefore, this study aims to develop a mathematical model to optimize the shipping process by assessing the textile product damage rate against environmental parameters such as humidity and temperature and shipping parameters such as shipping duration. The model developed using the Response Surface Methodology (RSM) statistical approach is based on linear and nonlinear models. The results showed that the linear model had a better coefficient of determination as a model validation parameter, with a coefficient of determination of 0.83. This value shows the effectiveness of optimizing the shipping process as a monitoring effort to determine the damage to textile products against several parameters that affect it. The results of this study have implications for the field of textile science, especially regarding the dynamics of distribution or logistics, as well as the application of mathematical applications in the textile field. In addition, the practical implications of this research are expected to be used as a monitoring effort for the textile industry to determine the impact of environmental parameters and shipping duration on the products they ship.